Pengaruh Lama Fermentasi dengan Kultur Mikroba Asam Laktat (Lactobacillus sp.) dan Teknik Roasting terhadap Kopi Arabika (Coffea arabica) - Lenny Amelia HK; Tanty Sulistiani Widodo (Ma'soem University, 2026)
Arabica coffee is celebrated for its unique flavor profile, yet enhancing its global market competitiveness requires innovation in post-harvest processing. Fermentation using lactic acid bacteria (LAB) specifically Lactobacillus plantarum and Lactobacillus brevis holds promise for modifying the coffee’s flavor, boosting acidity, and enriching its aroma and flavor complexity. However, the use of this technique in Arabica coffee processing remains limited. This study therefore aims to examine how LAB fermentation and roasting techniques influence the quality of Arabica coffee. The key controlled variables were fermentation duration (0, 12, 48, and 72 hours) and roasting method, which included light roast (160°C), medium roast (180°C), and dark roast (200°C). The experiment followed a Factorial Randomized Complete Block Design (RCBD) with a 4×3 factorial arrangement and three replications, yielding a total of 36 experimental units. Data were analyzed using Analysis of Variance (ANOVA) as part of a quantitative descriptive analysis. Based on the research findings, it can be concluded that fermentation time, roasting technique, and their interaction significantly affect the pH and moisture content of Arabica coffee beans. Meanwhile, roasting technique alone significantly influences caffeine content. The optimal treatment identified in this study was Arabica coffee beans fermented with Lactobacillus plantarum for 24 hours followed by medium roasting (180°C), which yielded a pH of 5.18, moisture content of 3.77%, caffeine content of 1.20%, a cupping score of 78.35, and a chlorogenic acid (CGA) content of 18.16 mg/g of roasted coffee beans.